Silene goksuensis (Caryophyllaceae), a new species from south Turkey - Budak, Ümit; Koç, Murat; Hamzaoğlu, Ergin (Phytotaxa, 2018)
A new species—Silene goksuensis—was described from Ermenek (Turkey, Karaman province) where it grows on rock crevices. As a result of examining the literature and herbarium specimens, It was found that the collected new species is morphologically related to S. longipetala from which it differs from in having glabrescent to very sparsely pilose below (short retrorsely pubescent below in S. longipetata), the basal leaves oblanceolate-spathulate (not obovate or oblanceolate) Description, distribution, conservation status, and original photos of the new species are given.